2009
DOI: 10.1002/elps.200800653
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic chips for protein differential expression profiling

Abstract: Biomarker discovery and screening using novel proteomic technologies is an area that is attracting increased attention in the biomedical community. Early detection of abnormal physiological conditions will be highly beneficial for diagnosing various diseases and increasing survivability rates. Clearly, progress in this area will depend on the development of fast, reliable, and highly sensitive and specific sample bioanalysis methods. Microfluidics has emerged as a technology that could become essential in prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 43 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…A microfluidics based chip-LC-MS system, devised by Horvatovich et al (2007) for application in label-free profiling of immunodepleted, trypsin-digested human serum, was found to give two times higher resolution compared to capillary LC-MS and required around 30 times less sample (Table 1). Armenta et al (2009) similarly reported the use of LC-ESI-MS for detection of MCF-7 breast cancer cellular extracts where they successfully identified 40-100 proteins from just 0.1-1 g of crude protein extract tryptic digest. These studies indicate the far-reaching impact that microfluidics will continue to have on sensitive and reliable mass spectrometric studies.…”
Section: Microfluidicsmentioning
confidence: 92%
“…A microfluidics based chip-LC-MS system, devised by Horvatovich et al (2007) for application in label-free profiling of immunodepleted, trypsin-digested human serum, was found to give two times higher resolution compared to capillary LC-MS and required around 30 times less sample (Table 1). Armenta et al (2009) similarly reported the use of LC-ESI-MS for detection of MCF-7 breast cancer cellular extracts where they successfully identified 40-100 proteins from just 0.1-1 g of crude protein extract tryptic digest. These studies indicate the far-reaching impact that microfluidics will continue to have on sensitive and reliable mass spectrometric studies.…”
Section: Microfluidicsmentioning
confidence: 92%
“…[103][104][105][106][107][108][109][110][111][112][113] Among these methods, optical and electrochemical methods are the most frequently utilized due to their selectivity and sensitivity. Other than the above major methods, approaches such as nuclear magnetic resonance (NMR) spectroscopy, [114][115][116][117][118] magnetoresistive, 119 and acoustical 120,121 are also coupled to microfluidics for sensing application.…”
Section: Detection Methodsmentioning
confidence: 99%
“…104-106) and matrix-assisted laser desorption ionization (MALDI)-MS. [107][108][109] In 2006, another paradigm is ion trap mass spectrometry integrated with microfluidics for protein identification by Hardouin et al 111 Other systems were also reported, such as a chip-liquid chromatography (LC)-MS system for labelfree profiling of human serum 113 and a LC-ESI-MS system for multiple proteins detection from breast cancer cellular extract. 112 The resolving ability of MS has recently been pushed down to the detection of a single molecular by Roukes's group in Caltech using a nanoelectromechanical system-based MS (NEMS-MS) (Fig. 6).…”
mentioning
confidence: 99%
“…Among the diverse classes of nanomaterials, the quantum dots, gold nanoparticles, carbon nanotubes and silicon nanowires are promising candidates for cancer biomarker detection. In addition to these widely used nanoproteomic tools for the cancer biomarker detection, there are other nanomaterial-based potential approaches as well, which include microcantilivers [58,59], microfluidics [60][61][62][63], photonic microring resonators [64], gold nanowires [65], silver nanoparticles [41], nanomechanical resonators [66], optofluidic ring resonator sensors [67] and suspended microchannel resonators [68] ( Table 2). The technological aspects and working principles of commonly used nanoproteomics techniques for cancer diagnosis have been discussed in detail in other reviews [28,[69][70][71].…”
Section: Nanoproteomics For Cancer Biomarker Detectionmentioning
confidence: 99%